An Aureus of Pompeius Magnus*. (8th February 2017) - Marshall, Bruce
Abstract: In a recent article in this journal, Kathryn Welch and Hannah Mitchell examined a much debated question: to what extent did Roman commanders, and in particular Pompeius, model themselves on Alexander the Great? 1 The opposing views on this question are best encapsulated by Peter Green on the one side, and Erich Gruen on the other. 2 One piece of evidence used in this continuing debate is an aureus of Pompeius, but there are two disputes related to it: the date of its issue and the iconography of its obverse. Unfortunately, due to a lack of specific evidence the discussion trying to resolve these disputes often ends without a clear conclusion, and we are left with speculation and conjecture. The reverse of the aureus shows a triumph, and the nub of the question about dating the coin is which triumph does it depict. The argument here is that the coin depicts Pompeius' third triumph in 61 BC, when he celebrated his extensive conquests in the East. That date will help the argument that the personification on the obverse has Alexander overtones, as some scholars suggest. If that can be established, it will give some idea of Pompeius' intentions in minting the coin: Pompeius was not only channelling Alexander, but also trying to imply that he had surpassed the Macedonian king's achievements.